Issues of Gender Inequality Depending on The Level of Education in The Czech Republic - Kamila VESELA; David KRIZEK (Communications of International Proceedings, 2022)
The gender wage gap is in the 21st century actual problem in all countries all over the world. Although in some areas the Czech Republic is doing well (access to education for men and women), in other areas the Czech Republic does not reach satisfactory level (especially gender wage gap or women´s participation in public decision-making). The aim of this text is to analyse and evaluate the state and development of gender wage gap in the Czech Republic. The emphasis is placed on the role of education on gender wage gap. This paper thus answers the question of the role of the highest educational attainment to gender wage gap. This can help to analyse the motivation for education of men and women as well as the effects of gender wage gap on the economy.
Keywords: average wage; gender wage gap; median wage.